Improving Junior High School Students' Mathematical Understanding Ability Through Powerpoint Assisted Visual Media - Rusdian Rifai; Turmudi; Jarnawi Afgani Dahlan; Suhendra (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Students typically have less interest in learning mathematics because it is still seen as a challenging subject. As a result, when compared to other disciplines, the pupils' mathematics understanding abilities remained below average. The aim of this study was to find out how employing visual aids, such as PowerPoint, to teach geometric shapes to students improved their mathematical comprehension skills. This kind of study uses a random subject posttest design and is therefore quasi-experimental. The population of this study consisted of students in class VIII SMPN 1 Pagelaran; the samples were drawn using the purposive sampling technique from students in class VIII C, which was the experimental class, and class VIII D, which was the control class. The t-test, homogeneity test, and normalcy test are the data analysis methods employed. With a significant rate of0.05, the testing results for the hypothesis produced tstat= 3.2 > ttable= 1.6801. This indicates that while Ha is acceptable, Ho is denied. This demonstrates how employing PowerPoint-assisted visual aids in mathematics instruction increases students' capacity for mathematical knowledge.